SAT0162 WITHDRAWAL OF LOW-DOSE STEROIDS IN SYSTEMIC LUPUS ERYTHEMATOSUS IN REMISSION: PREDICTORS OF FLARES AND DIFFERENCE IN OUTCOMES IN SEROLOGICALLY ACTIVE CLINICALLY QUIESCENT PATIENTS. (2nd June 2020) - Fasano, S.; Pierro, L.; Coscia, M. A.; Bucci, L.; Scriffignano, S.; Riccardi, A.; Ciccia, F.
Abstract : Background: According to the recent recommendations for Systemic Lupus Erythematosus (SLE), a progressive tapering until withdrawal of glucocorticoids (GC) is considered one of the main goals of SLE management (1). However, which patient may be a candidate for safe GC withdrawal has not been determined yet and a proportion of patients are kept on long-term low-dose prednisone despite clinical remission. Objectives: to evaluate the rate of low-dose GC withdrawal in SLE patients in remission and to identify predictors of flares. Methods: Eligible patients were SLE patients according to the ACR criteria (2) who were in prolonged clinical remission defined by a cSLEDAI=0 for at least 2 years and on a stable SLE treatment (immunosuppressive drugs and/or hydroxychloroquine (HCQ) and daily 5 mg prednisone). A SACQ period was defined as at least 1-year period with persistent serologic activity without clinical manifestations. Flares were defined by SELENA-SLEDAI Flare Index (3). Damage was assessed by SLICC damage index (SDI). Data were compared by the unpaired student's t test or chi-squared test as appropriate. Predictors of flares after GC withdrawal were analyzed by Cox regression. Results: Out of 246 SLE patients registered in the Naples Lupus Clinic database, 132 eligible patients were identified. Among them, we selected 57 (43%) patients in whom a GC withdrawal was attempted. 75 (57%) patients were in the prednisone maintenance group. There were no significant differences between the two treatment groups (table 1 ). The proportion of patients experiencing a flare was not significantly lower in the maintenance group than in the withdrawal group (15/75 vs 16/57; p=0.28). Moreover, the proportion of patients who had an increase in the SDI at the end of follow up was similar between the two groups (14/75 vs 8/57; p=0.48). However, among the withdrawal group, the rate of flares was significantly higher in SACQ patients (10/22 vs 6/35; p=0.02), while the majority of serologically inactive patients (82%) successfully stopped GCs without subsequent flares. At Cox regression analysis (Table 2 ), duration of HCQ therapy and >4 year remission at withdrawal were protective factors, while a SACQ disease and history of lupus nephritis (LN) increased the risk of disease flare. Conclusion: GC withdrawal is an achievable target in SLE and may be attempted in patients in complete remission. In SACQ patients, maintenance of 5mg prednisone is superior to its withdrawal in order to prevent flares. Long-term HCQ therapy and prolonged remission can significantly reduce the risk of disease relapse after GC withdrawal. References: [1]Fanouriakis A, et al. Ann Rheum Dis. 2019;78(6):736–45. [2]Tan EM, et al. Arthritis Rheum. 1982;25(11):1271–7. [3]Petri M, et al. Lupus. 1999;8(8):685–91. Disclosure of Interests: Serena Fasano: None declared, Luciana Pierro: None declared, Melania Alessia Coscia: None declared, laura Bucci: None declared, silvia scriffignano: None declared, Antonella Riccardi: None declared, francesco ciccia Grant/research support from: pfizer, novartis, roche, Consultant of: pfizer, novartis, lilly, abbvie, Speakers bureau: pfizer, novartis, lilly, abbvie